Integration of Digital Technology and Green Human Resource Management (GHRM) in Aligning Equity Principles to Drive Innovation, Employee Development, and Environmental Sustainability - Al Alaq, Ameera Sahar; Damayanti, Adinda Oktaviana; Efendi, Doni; Tahara, Ghina Thalita; Setyawati, Novita (Jurnal Ilmiah Manajemen dan Bisnis, 2025)
The integration of digital technology in the era of Industry 4.0, such as artificial intelligence (AI) and machine learning (ML), has driven green innovation in the manufacturing sector, improving operational efficiency, financial performance, and reducing environmental impact. However, the uneven distribution of sustainability benefits remains a challenge that requires strategic solutions. This study aims to analyze how the application of equity principles in Green Human Resource Management (GHRM) can mediate the relationship between digital technology and organizational sustainability. The study employs a literature-based methodology with research result reporting to examine the contribution of equity-based GHRM in supporting organizational sustainability. Relevant literature is identified and analyzed to explore the role of equity principles in providing equal access to green training, skill development, and the distribution of sustainability benefits. This methodology enables a comprehensive understanding of the relationship between GHRM, digital technology, and sustainability. The findings indicate that equity principles in GHRM enhance employee engagement and commitment to green initiatives through an inclusive and collaborative work environment. Digital technologies such as E-HRM and AI facilitate efficient green training, reduce carbon footprints, and strengthen organizational competitiveness. This approach also addresses gaps in access to training and development, reinforces an environmentally friendly work culture, and boosts employee productivity. In conclusion, integrating equity principles into GHRM and leveraging digital technologies create a strategic approach to achieving environmental, social, and economic sustainability. This study highlights the importance of combining equity and technology in building a holistic, progressive, and inclusive sustainability strategy to address future global challenges.